2021
DOI: 10.1007/s12144-021-02452-6
|View full text |Cite
|
Sign up to set email alerts
|

Is mHealth a useful therapy for improving physical or emotional health in adolescents with cystic fibrosis? A systematic review

Abstract: Cystic fibrosis (CF) is a rare disease that severely compromises health and interferes with the lives of those who suffer from it and is especially challenging in adolescence. The use of tools such as MHealth may benefit the physical and psychological health of adolescents with CF. Therefore, this study aims to examine the benefits of MHealth in adolescents with CF through a systematic review. A search of the scientific literature following the PRISMA guidelines was conducted in the ProQuest Central, PubMed, W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Although a recent review of the literature [ 36 ] on the use of mobile devices (phones, patient monitoring devices, digital assistants, and other wireless devices) by patients with CF has shown medical, psychological, and behavioral benefits as well as benefits in terms of level of satisfaction with care, the psychological aspect has thus far received little attention, as is the case with the educational dimension of technological devices. In adolescence, although the disease significantly influences the development of one’s body image and self-concept [ 37 ], the integration of new technologies into self-care leads to a new understanding of oneself and, therefore, to a potentially modified relationship with one’s body, health, and illness.…”
Section: Discussionmentioning
confidence: 99%
“…Although a recent review of the literature [ 36 ] on the use of mobile devices (phones, patient monitoring devices, digital assistants, and other wireless devices) by patients with CF has shown medical, psychological, and behavioral benefits as well as benefits in terms of level of satisfaction with care, the psychological aspect has thus far received little attention, as is the case with the educational dimension of technological devices. In adolescence, although the disease significantly influences the development of one’s body image and self-concept [ 37 ], the integration of new technologies into self-care leads to a new understanding of oneself and, therefore, to a potentially modified relationship with one’s body, health, and illness.…”
Section: Discussionmentioning
confidence: 99%
“…Pilot data from these studies also demonstrate that the online CF-CBT program was both feasible and acceptable ( 27 ). In addition to the sparsity of available research for this CF focus, a systematic review in 2021 investigating mHealth apps for CF emotional and physical health concluded that current available research was of low quality due to small sample sizes, limited to pilot studies, and with homogeneity in data ( 28 ).…”
Section: Virtual Monitoring In Cf Carementioning
confidence: 99%